BRCA1-associated R-loop affects transcription and differentiation in breast luminal epithelial cells. Issue 10 (15th April 2019) - Chiang, Huai-Chin; Zhang, Xiaowen; Li, Jingwei; Zhao, Xiayan; Chen, Jerry; Wang, Howard T-H; Jatoi, Ismail; Brenner, Andrew; Hu, Yanfen; Li, Rong
Abstract: BRCA1 -associated basal-like breast cancer originates from luminal progenitor cells. Breast epithelial cells from cancer-free BRCA1 mutation carriers are defective in luminal differentiation. However, how BRCA1 deficiency leads to lineage-specific differentiation defect is not clear. BRCA1 is implicated in resolving R-loops, DNA-RNA hybrid structures associated with genome instability and transcriptional regulation. We recently showed that R-loops are preferentially accumulated in breast luminal epithelial cells of BRCA1 mutation carriers. Here, we interrogate the impact of a BRCA1 mutation-associated R-loop located in a putative transcriptional enhancer upstream of the ERα-encoding ESR1 gene. Genetic ablation confirms the relevance of this R-loop-containing region to enhancer-promoter interactions and transcriptional activation of the corresponding neighboring genes, including ESR1, CCDC170  and RMND1 . BRCA1 knockdown in ERα+ luminal breast cancer cells increases intensity of this R-loop and reduces transcription of its neighboring genes. The deleterious effect of BRCA1 depletion on transcription is mitigated by ectopic expression of R-loop-removing RNase H1. Furthermore, RNase H1 overexpression in primary breast cells from BRCA1 mutation carriers results in a shift from luminal progenitor cells to mature luminal cells. Our findings suggest that BRCA1-dependent R-loop mitigation contributes to luminal cell-specific transcription and differentiation, which could in turn suppress BRCA1 -associated tumorigenesis.